2002
DOI: 10.1002/bem.10059
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of Paramecium swimming in a DC magnetic field

Abstract: We found that a ciliated protozoan, Paramecium, swam perpendicular to a static (DC) magnetic field (0.68 T). The swimming orientation was similar even when the ionic current through the cell membrane disappeared after saponin treatment. To determine the diamagnetic anisotropy of intracellular organs, macronuclei, cilia, and secretory vesicles, trichocysts, were selectively isolated. Both cilia and trichocysts tended to align their long axis parallel to the magnetic field (0.78 T). Paramecium mutants that lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Parallel swimming of P. caudatum with respect to the direction of the applied strong magnetic field (*3 T) (Fujiwara et al, 2006;Valles, 2006a, 2006b), as well as perpendicular swimming of P. aurelia to a static magnetic field of moderate intensity (0.68 T) (Nakaoka et al, 2002), has been observed. Tanimoto et al (2002) described magnetotaxis of E. gracilis in a horizontal magnetic field gradient.…”
Section: Magnetic Levitation Versus Real Microgravity-the Biological mentioning
confidence: 97%
See 1 more Smart Citation
“…Parallel swimming of P. caudatum with respect to the direction of the applied strong magnetic field (*3 T) (Fujiwara et al, 2006;Valles, 2006a, 2006b), as well as perpendicular swimming of P. aurelia to a static magnetic field of moderate intensity (0.68 T) (Nakaoka et al, 2002), has been observed. Tanimoto et al (2002) described magnetotaxis of E. gracilis in a horizontal magnetic field gradient.…”
Section: Magnetic Levitation Versus Real Microgravity-the Biological mentioning
confidence: 97%
“…In a previous study, this group also investigated isolated cell organelles with respect to their diamagnetic anisotropy and thus orientation within a static magnetic field of 0.78 T; cilia as well as trichocyts oriented in parallel, while isolated macronuclei showed no tendency to align. Thus, orientation is determined by the diamagnetic anisotropy of the cell organelles (Nakaoka et al, 2002).…”
Section: Reason For Alignmentmentioning
confidence: 99%
“…However, it has been observed that magnetic fields affect swimming behavior of different species of Ciliates. The movement pattern appears to be altered both by ELF-EMFs (50 Hz, 0.5-2 mT; 60 Hz, 0.6 T) [Hemmersbach et al, 1997;Nakaoka et al, 2000] and static magnetic fields (0.126 T, 0.68 T) [Rosen and Rosen, 1990;Nakaoka et al, 2002]. Studies on cell population growth have revealed significant decreases in the growth rate of Amoeba hatchetti, A. castellanii, and A. polyphaga exposed to a uniform static magnetic field (71 or 106.5 mT) [Berk et al, 1997], as well as of Physarum polycephalum exposed to a 75 Hz magnetic field [Marron et al, 1975;Greenebaum et al, 1982]; conversely, a 72 Hz EMF increased cell fission rate in Paramecium [Dihel et al, 1985].…”
Section: Introductionmentioning
confidence: 97%
“…Taking into account the above molecular behaviors, Paramecium, which is constituted of these heterogeneously organized diamagnetic substances, would be expected to undergo magnetic orientation. Such an approach has already been investigated by Nakaoka et al [2002], whereby K þ -hyperpolarized Paramecium cells exposed to a 0.68 T static DC field were found to orient themselves perpendicular to the magnetic field within a few seconds of exposure. The constant effort applied to escape from the influence of the magnetic force, which is directed perpendicularly to the direction of the field and direction of the motion, could increase the stress load of the organism due to the high-energy demand of the process.…”
Section: Discussionmentioning
confidence: 98%
“…The effects of magnetic fields on swimming behavior of Paramecium have been studied previously [Rosen and Rosen, 1990;Nakaoka et al, 2002]. Changes in swimming activities are related to the structure of the Paramecium cortex.…”
Section: Discussionmentioning
confidence: 99%